Synthesis and electrocatalytic properties of M (Fe, Co), N co-doped porous carbon frameworks for efficient oxygen reduction reaction. (22nd February 2022) - Zhu, Zhaoqi; Cui, Jie; Cao, Xiaoying; Yang, Lijuan; Sun, Hanxue; Liang, Weidong; Li, Jiyan; Li, An
Abstract: The exploitation of high efficiency non-precious metal electrocatalysts towards oxygen reduction reaction (ORR) is great significant for large-scale commercialization of next-generation fuel cells. In this work, we designed and fabricated a series of porous carbazole-based N and M (Co, Fe) doped carbon framework catalysts which were obtained by the pyrolysis of a N-rich hypercrosslinked polymers derived from Friedel–Crafts reaction (abbreviated as TSP-HCP-900) followed by the incorporation of metal into the as-resulted N rich carbon (abbreviated as M-TSP-HCP-900, M = Co, Fe). Based on the high specific surface, excellent porosity, large pyridine nitrogen content and synergistic catalytic effects between the N dopants and metal nanoparticles, the M-TSP-HCP-900 exhibited superior ORR catalytic activity. Among them, the Co-TSP-HCP-900 possesses better electrocatalysis, i.e., a high diffusion limiting current density of 4.74 mA cm −2, half-wave potential of 0.8 V (vs. RHE, the same below) and onset potential of 0.9 V were found, respectively. In addition, this catalyst also discloses an excellent methanol tolerance, better durability and a biased 4e − reaction pathway, which are comparable to state-of-the-art Pt/C catalysts. Taking advantage of mentioning above, the M-TSP-HCP-900 may hold great potentials as promising alternative of precious metal catalysts for electrochemical energy conversion and storage. Highlights: Transition metal and nitrogen co-doped carbon (M-N/C) were prepared as non-precious ORR electrocatalysts. It yields a half-wave potential of 0.80 V and onset potential of 0.90 V (vs. RHE) in alkaline medium. It exhibits a high diffusion limiting current density of 4.74 mA cm −2 . It shows better stability and methanol resistance than that of commercial 20 wt% Pt/C.